2018
DOI: 10.1038/s41419-018-0810-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Notch1 and AKT mediated epithelial to mesenchymal transition by Verrucarin J in metastatic colon cancer

Abstract: Epithelial to mesenchymal transition (EMT) in colorectal cancer (CRC) has been attributed to activation of AKT and Notch1 signaling pathways. As EMT corresponds to increased aggressiveness of CRC, approaches that prevent metastasis by targeting AKT/Notch1 pathways are at the forefront of current research paradigms. This study examined the anti-metastatic potential of Verrucarin J (VJ), a small molecule, in CRC cells overexpressing AKT and Notch1. VJ significantly inhibited AKT/HCT 116 cell growth by acting on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Phosphorylation of AKT is a key step in the activation of AKT pathway. Studies have shown that hyperactivation of AKT can lead to EMT in in vitro and in vivo CRC models [33]. In our study, we found the level of p-Akt was up-regulated in colon cancer cells with FABP4 overexpression.…”
Section: Discussionsupporting
confidence: 61%
“…Phosphorylation of AKT is a key step in the activation of AKT pathway. Studies have shown that hyperactivation of AKT can lead to EMT in in vitro and in vivo CRC models [33]. In our study, we found the level of p-Akt was up-regulated in colon cancer cells with FABP4 overexpression.…”
Section: Discussionsupporting
confidence: 61%
“…As previously mentioned, Notch1 also plays a critical role in the development of EMT (Pal et al, 2018). The Jagged1/Notch1 signaling pathway was therefore also explored.…”
Section: Rpyd Reduces Emt By Inhibiting the Jagged1/notch1 Signaling mentioning
confidence: 99%
“…NICD can enter the nucleus and combine with the DNA-binding protein RBP-Jκ (also known as CSL) to form a complex that initiates the transcription process of target genes such as Hes1 (LaFoya et al, 2016). Notch1 is involved in the development of EMT in tumor and lung fibrosis models (Pal et al, 2018;Yin et al, 2018). In addition, TGF-β and Notch pathways are synergistically involved in regulating Hes1 expression (Blokzijl et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…ting. Annexin V-fluorescein isothiocyanate (FITC) against propidium iodide (PI) assay (FITC Annexin V Apoptosis Detection Kit I, BD Pharminogen) was used for detecting apoptosis as described previously (17). Total protein extracts from TCCSUP cells were prepared with the Mammalian Protein Extraction Reagent (Thermo Scientific) according to the manufacturer's instructions.…”
Section: Detection Of Apoptosis By Flow Cytometry and Immunoblot-mentioning
confidence: 99%
“…Based on the structure-activity relationship studies focused on the Withaferin A (a dietary compound which exhibits anti-cancer effect against many cancer types) (16)(17)(18)(19)(20)(21)(22) analogs designed in our laboratory, we have identified a novel small molecule, ASR488, designed by protecting-OH group at 4-position of Withaferin A by thiophene-2-carbonyl functionality. ASR-488 demonstrated cell growth arrest in BCa cells and, more importantly, is non-toxic to normal BCa cells.…”
Section: Introductionmentioning
confidence: 99%